Correlation of biochemical and anthropometric parameters with tooth loss in older adults - Wagner Couto Assis; Mateus Cardoso Oliveira; Jennifer Santos Pereira; Lucas dos Santos; Patricia Elizabeth Souza Matos; Cezar Augusto Casotti (Acta Scientiarum. Health Sciences)
This study estimated the impact of tooth loss on biochemical parameters and anthropometric indicators of adiposity in older adults. A three-step data collection was conducted. First, trained interviewers applied a questionnaire for collecting sociodemographic and economic information to people aged 60 or over, in their households. Second, a dental surgeon and a physical educator assessed the oral condition and anthropometric measurements. Finally, biochemists obtained blood samples to analyze biochemical parameters. Descriptive analyses, Pearson’s correlation, and multiple linear regression were performed using SPSS and STATA software. A total of 117 older adults, mean age of 71.2 years, were evaluated, 62.4% of whom were female. Cavities had a 100% prevalence, average DMFT index was 27.8, and missing component was the most prevalent (24.8). The final regression model found a correlation between tooth loss and females, vitamin B12, glycated hemoglobin, and magnesium. Older adults living in Aiquara showed a correlation between tooth loss and females, vitamin B12, glycated hemoglobin, and magnesium.